2019
DOI: 10.6004/jnccn.2018.7082
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Randomized Controlled Trials of Exercise Interventions Using Digital Activity Trackers in Patients With Cancer

Abstract: Background Exercise can ameliorate cancer- and treatment-related toxicities, but poor adherence to exercise regimens is a barrier. Exercise interventions using digital activity trackers (E-DATs) may improve exercise adherence, but data are limited for patients with cancer. We conducted a systematic review examining the feasibility of E-DATs in cancer survivors and effects on activity level, body composition, objective fitness outcomes, health-related quality of life (HRQoL), self-reported symptoms, and biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 64 publications
2
47
1
Order By: Relevance
“…Because wearable devices offer data and feedback directly to patients, these tools are also used to promote physical activity among cancer patients and survivors 32 . Two recent reviews of studies using wearable devices to promote activity among cancer survivors found that interventions using wearable activity monitors had a positive impact on physical activity as well as symptoms and quality of life 33 , 34 . Moreover, real-time wearable device data may allow for tailored or just-in-time physical activity interventions 35 that may be further enhanced by the support of a coach who can review a patient’s real-time data and provide individualized support for behavior change 36 .…”
Section: Consumer Wearable Devices In Oncology Researchmentioning
confidence: 99%
“…Because wearable devices offer data and feedback directly to patients, these tools are also used to promote physical activity among cancer patients and survivors 32 . Two recent reviews of studies using wearable devices to promote activity among cancer survivors found that interventions using wearable activity monitors had a positive impact on physical activity as well as symptoms and quality of life 33 , 34 . Moreover, real-time wearable device data may allow for tailored or just-in-time physical activity interventions 35 that may be further enhanced by the support of a coach who can review a patient’s real-time data and provide individualized support for behavior change 36 .…”
Section: Consumer Wearable Devices In Oncology Researchmentioning
confidence: 99%
“…Ambulatory physiological recordings have also demonstrated utility performing dynamic assessments of symptoms over time in patients with cancer (Savard et al, 2013), Parkinson's disease (Moore et al, 2008), Autism Spectrum Disorder (Goodwin et al, 2019), borderline personality disorder (Ebner-Priemer et al, 2008), and seizures (Michel et al, 2015). Telemetric devices are also beginning to be used to deliver interventions to treat symptoms or disease (e.g., exercise interventions for patients with cancer; Schaffer et al, 2019).…”
Section: Framework For Selecting and Benchmarking Mobile Devices In Pmentioning
confidence: 99%
“…However, these technologies are still in the very early stages of development and adoption in breast cancer rehabilitation. To date, innovations have mainly focused on physical activity interventions [ 40 - 42 ], lymphedema management [ 28 ], psychological well-being [ 43 ], and general survivorship care [ 29 , 44 ]. Very few interventions concentrate on physiotherapy rehabilitation exercises.…”
Section: Introductionmentioning
confidence: 99%